Hukuman Kebiri bagi Pelaku Pedofilia dalam Perspektif Hak Asasi Manusia - Marbun, Paulina; Husodo, Jadmiko Anom (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTIndonesia is one of the countries that often experience child sexual abuse. The cases number significantly increase. The regulations in law Number 35 of 2014 concerning Child Protection are unable to provide a deterrent effect on perpetrators of child sexual abuse. That’s why chemical castration punishment was born. The application of this punishment becomes controversial, some people thought it was appropriate to have a deterrent effect. But on the other hand, this punishment is  considered to violate human rights. The problem in this research is: Does chemical  castration punishment for pedophiles violate human rights?  and what’s the ideal castration punishment to not to violate human rights? the research method used is normative legal research. The purpose of this study is to find out whether castration punishment violates human rights and to find out the ideal way of chemical castration punishment. The theoretical benefit of this research is to develop science, especially in human rights. while the practical benefits of this research are the consideration of the stakeholders in making government regulations related to the method of implementing castration punishment in Indonesia.Keywords  : human rights; chemical castration; sexual abuse.